A STUDY ON IMPACT OF SOCIAL MEDIA ON VIRTUAL YOGA COMMUNITY (International Journal of Food and Nutritional Sciences, 2022)
The yoga community on social media refers to the network of individuals, yoga practitioners, instructors, influencers and studios who engage with and share yoga related content on various social media platforms. This community encompasses people of all levels of experience and can be found on platforms such as Instagram, YouTube, Facebook , etc. Within the yoga community on social media, you'll find a wide range of content, such as Yoga Pose Demonstrations, Yoga Challenges, Inspirational Quotes and Messages, Educational Content, etc. The yoga community on social media fosters connections, supports learning, and provides inspiration for practitioners around the world. However, as with any online community, it's essential to approach social media with caution and critically evaluate the information and content shared to ensure a safe and positive experience. When it comes to Yoga, Social Media has played the role of both, blessing as well as a curse. Social Media is a blessing to Yoga as it has helped to spread the awareness of Yoga, not just in India but all around the world.